2020
DOI: 10.21315/tlsr2020.31.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Extraction Condition of Clitorea ternatea Flower on Antioxidant Activities, Total Phenolic, Total Flavonoid and Total Anthocyanin Contents

Abstract: Clitoria ternatea is a herbaceous plant with many health benefits. Extraction is crucial to obtain its bioactive components which contribute to its antioxidant properties. Therefore, this study was conducted to find an optimum extraction condition of C. ternatea flower on total phenolic content (TPC) and antioxidant activity (2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical-scavenging activity) as well as to determine its total flavonoid content (TFC) and anthocyanin content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 29 publications
(31 reference statements)
2
8
0
1
Order By: Relevance
“…Previous investigations conducted on optimizing extraction parameters for phenolic and anthocyanin extraction from C.ternatea flowers through different techniques reports data similar to those obtained from the present work. Optimized temperature for ultrasound assisted extraction of phenolics from C.ternatea flowers was reported to be 50°C, 24 similarly Jaafar et al, 25 has identified that the optimum ethanol concentration and extraction temperature for phenolic extraction from C.ternatea flowers as 39.62% and 44.24°C respectively which was close to the values obtained from our work. The findings of the current study may be useful for the food industry and pharmaceutical analysis to directly apply the optimized conditions so that it can reduce the cost and labor‐intensive process with efficient extraction of antioxidant compounds.…”
Section: Discussionsupporting
confidence: 89%
“…Previous investigations conducted on optimizing extraction parameters for phenolic and anthocyanin extraction from C.ternatea flowers through different techniques reports data similar to those obtained from the present work. Optimized temperature for ultrasound assisted extraction of phenolics from C.ternatea flowers was reported to be 50°C, 24 similarly Jaafar et al, 25 has identified that the optimum ethanol concentration and extraction temperature for phenolic extraction from C.ternatea flowers as 39.62% and 44.24°C respectively which was close to the values obtained from our work. The findings of the current study may be useful for the food industry and pharmaceutical analysis to directly apply the optimized conditions so that it can reduce the cost and labor‐intensive process with efficient extraction of antioxidant compounds.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, when anthocyanins from blue pea flowers are extracted for food application, the use of hazardous organic solvents should be avoided (Khoo et al, 2017;Chemat et al, 2019). Several studies have used hydro alcoholic extraction [i.e., 37% ethanol (Jaafar et al, 2020), 50% ethanol (Pham et al, 2019), 50% methanol (Shen et al, 2019)] to extract anthocyanins from blue pea flower. However, FDA (2018) has categorised methanol as a class 2 solvent having inherent toxicity and ethanol as a class 3 solvent that should be limited by good manufacturing practices (GMP) and other quality-based requirements.…”
Section: Extraction Of Blue Pea Flower Anthocyaninsmentioning
confidence: 99%
“…The nature factors such as climate and soil characteristics, the presence of antimicrobial agents, and mode of action will affect the pharmacological activities from different parts of the butterfly pea. According to butterfly pea morphological variations in Indonesia, to identify the optimum extraction condition, high amount of bioactive chemicals and antioxidants, numerous crit-ical aspects such as the solvent, extraction duration, and temperature should be considered as main factors (Jaafar et al 2020). Another suggestion, combination with other herbs that favour as traditional medicine in Indonesia, can achieve a safe and effective oral hygiene aid with orthodontics herbal-based products to anticipate the susceptible to reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%